2014
DOI: 10.1016/j.jval.2014.03.1488
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for frequency of glucagon-like peptide-1 receptor agonist (GLP-1RA) injections in the treatment of type 2 diabetes

Abstract: Objectives: Anti-diabetics have varying efficacy and safety profiles. This study aimed to better understand patient preferences for oral anti-diabetics by examining the relative importance (RI) of medication attributes that influence treatment selection among patients in the US with type 2 diabetes mellitus (T2DM). MethOds: A web-based discrete choice experiment (DCE) was developed to assess the RI of 7 medication attributes (effectiveness, hypoglycemia, weight change, gastrointestinal/nausea side effects [SE]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Frequency of injection (weekly vs daily) was identified as the most important feature among hypothetical GLP1-receptor-agonist profiles in a patient-preference survey of 184 injection-naïve patients with type 2 diabetes. 67 The survey included a series of 10 questions regarding a pair of hypothetical GLP1-receptor agonists with equivalent efficacy and adverse events, but with different profiles otherwise. Preferences for all other GLP1-receptor-agonist attributes (eg, type of injection device) in this discrete-choice experiment were dependent on frequency of injection (ie, the estimated preference parameter on the interaction between injection frequency and each treatment feature was statistically significant).…”
Section: Strategies To Improve Adherence To Antihyperglycemic Medicatmentioning
confidence: 99%
“…Frequency of injection (weekly vs daily) was identified as the most important feature among hypothetical GLP1-receptor-agonist profiles in a patient-preference survey of 184 injection-naïve patients with type 2 diabetes. 67 The survey included a series of 10 questions regarding a pair of hypothetical GLP1-receptor agonists with equivalent efficacy and adverse events, but with different profiles otherwise. Preferences for all other GLP1-receptor-agonist attributes (eg, type of injection device) in this discrete-choice experiment were dependent on frequency of injection (ie, the estimated preference parameter on the interaction between injection frequency and each treatment feature was statistically significant).…”
Section: Strategies To Improve Adherence To Antihyperglycemic Medicatmentioning
confidence: 99%
“…The literature review revealed a paucity of data relating to r-hGH injection treatment burden (the most-cited references were related to diabetes [39][40][41][42][43]) and identified several functional health domains (e.g., emotional, role, travel, physical function) that may be impacted by daily injection treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These attributes were selected because they are key differentiating characteristics and are consistent with relevant attributes included in previous studies of medication preferences among T2D populations. 9,[20][21][22][23][24][25][26][27][28] The attribute levels were defined based on the results of the SURPASS-2 trial (Table 1) which was a direct head-to-head study of tirzepatide 5mg, 10mg, and 15mg versus semaglutide 1mg. 17 The attribute levels shown within each treatment profile in the DCE were systematically varied based on an experimental design algorithm.…”
Section: Surveymentioning
confidence: 99%